2021
DOI: 10.1177/0031512520985760
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Athletes’ Perceptions of Both Their Coachs’ Leadership and Their Personal Motivation

Abstract: Previous studies, framed within the full range leadership approach, have described how the coach’s interpersonal behaviors affected athletic outcomes. However researchers have yet to explore how specific leadership behaviors (transformational vs transactional), as perceived by athletes, may affect athletes’ motivation. The aim of this study was to further examine the link between coaches’ leadership behaviors and athletes’ motivation among high achieving adolescent athletes. Two-hundred and twenty-three elite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 50 publications
1
9
0
2
Order By: Relevance
“…Such findings may not be surprising, as transformational leadership behaviours in sport highlight the value of different roles and showing appreciation for athlete efforts (Turnnidge and Côté, 2019a). The findings can also be considered in line with previous empirical works, as studies have found positive associations between transformational leadership and elite youth athletes' intrinsic motivation (Subijana et al, 2021), and that transformational leaders generally tend to have satisfied followers across contexts (Judge and Piccolo, 2004;Kao and Tsai, 2016).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Such findings may not be surprising, as transformational leadership behaviours in sport highlight the value of different roles and showing appreciation for athlete efforts (Turnnidge and Côté, 2019a). The findings can also be considered in line with previous empirical works, as studies have found positive associations between transformational leadership and elite youth athletes' intrinsic motivation (Subijana et al, 2021), and that transformational leaders generally tend to have satisfied followers across contexts (Judge and Piccolo, 2004;Kao and Tsai, 2016).…”
Section: Discussionsupporting
confidence: 85%
“…While youth sport groups have been the primary focus of transformational coaching research in sport, Arthur et al (2017) noted in their review that most of the studies have been conducted on less skilled athletes. As a recent exception, Subijana et al (2021) investigated 223 elite youth athletes from a variety of sports and found positive associations between transformational leadership and intrinsic motivation. Further, Smith et al (2017) conducted a qualitative study on transformational leadership behaviours in an elite sport environment.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, the size of the sample, although unique, was small and the study may have deficient in statistical power detect smaller effects than f 2 ¼ .19. 33 Thirdly, about the tools, event though we applied the Spanish version of the DTLI-YS, 30 we did not measured the high performance expectations from the original DTLI 7 and this dimension could be relevant at elite sport level. 45 Also, we only considered the CART-Q as a direct measure of athletes' perceptions, we did no considered the metaperspective (i.e., the degree to which one relationship member can accurately infer the other member's closeness, commitment, and complementarity) to further understand the coorientation of the relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Coach leadership. We administered the Spanish version 30 of the Differentiated Transformational Leadership Inventory for Youth Sport (DTLI-YS ; 31]. The Spanish version of the DTLI-YS has 23-items within six subscales: contingent rewards (e.g., "My coach gives me special recognition when I do very good work"); fostering acceptance of group goals and teamwork (e.g., "My coach develops a strong attitude and spirit among team members"); appropriated role-model (e.g., "My coach leads from the front whenever he/she can"); intellectual stimulation (e.g., "My coach challenges me to think about problems in new ways"); inspirational motivation a (e.g., "My coach talks enthusiastically about what needs to be accomplished"); and individual consideration (e.g., "My coach recognizes that different players have different needs").…”
Section: Methodsmentioning
confidence: 99%
“…É do conhecimento geral que os jovens atletas, quando envolvidos em programas desportivos, podem ser profundamente influenciados pelos seus treinadores (SUBIJANA et al, 2021). O ingresso no desporto dá-se habitualmente quando a criança e o jovem saem do seu grupo familiar, ampliando os seus relacionamentos e reforçando a cooperação social.…”
Section: Introductionunclassified